Ground state of (Pb0.94Sr0.06)(Zr 0.530Ti0.470)O3 in the morphotropic phase boundary region: Evidence for a monoclinic Cc space group - Solanki R.S.; Singh A.K.; Mishra S.K.; Kennedy S.J.; Suzuki T.; Kuroiwa Y.; Moriyoshi C.; Pandey D. (My University, 2025)
The antiferrodistortive (AFD) phase transition for a pseudotetragonal composition of Pb(Zr0.530Ti0.470)O3 doped with 6% Sr has been investigated using sound velocity (4-320 K), high-resolution synchrotron x-ray powder diffraction (100-800 K), and high-resolution as well as high-flux neutron powder diffraction measurements (4 K) to settle the existing controversies about the true ground state of Pb(ZrxTi 1-x)O3 (PZT) in the morphotropic phase boundary (MPB) region. The multiplet character of the neutron diffraction profiles of (3/2 1/2 1/2)pc (pseudocubic or pc indices) and (3/2 3/2 1/2)pc superlattice peaks, appearing below the AFD transition temperature, rules out the rhombohedral R3c space group. The true ground state is confirmed to be monoclinic in the Cc space group, in agreement with the predictions of the first-principles calculations and earlier findings for pure PZT in the MPB region. Here, 6% Sr2+ substitution and the use of high-wavelength (λ = 2.44 Å) neutrons have played a key role in settling the existing controversies about the true ground state of PZT in the MPB region. © 2011 American Physical Society.